A Review on testing methods of recycled Acrylonitrile Butadiene-Styrene. (2018) - Manish,; Gurjar, Dharmendra; Sharma, Shubham; Akash,; Sarkar, Mayukh
Abstract: ABS (Acrylonitrile-Butadiene-Styrene) is an opaque thermoplastic polymer material made from the monomers Acrylonitrile, 1, 3-Butadiene and Styrene. It is a polymer made by polymerizing styrene (40% - 60%) and acrylonitrile (15% - 35%) in the presence of polybutadiene (5% - 30%). ABS is strong and durable even at low temperatures, it offers good resistance to heat and chemicals and is easy to process. To test its excellence of toughness, good dimensional stability, easy processing ability, and, chemical resistance different testing machines are acquired which is shown in this article. The aim of this article is to explain the different methods which can be used to investigate mechanical strength of ABS.